Pig with metal-hydride cathode under ion-stimulated desorbtion of hydrogen - Agarkov, A.V.; Ryabchikov, D.L.; Sereda, I.N.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2013)
The results of experimental investigation of penning type charged particles source with metal-hydride watercooled cathode are presented. The feature of investigation is hydrogen ion-stimulated desorbtion from metal-hydride as a way of working gas feeding. The influence of ion-stimulated desorbtion on emissive source characteristics was studied. In outflowing in axial direction charged particles flow the dynamic of energy distribution function of electrons and ions was carried out and their dependence on discharge external parameters was determined.